A Comparison of the Efficacy of Dry Needling, Lidocaine Injection, and Oral Flurbiprofen Treatments in Patients with Myofascial Pain Syndrome: A Double-Blind (For Injection, Groups Only), Randomized Clinical Trial - Pınar Küçük EROĞLU; Özlem YILMAZ; Hatice BODUR; Can ATEŞ2 (Archives of Rheumatology, 2013)
Objectives: The aim of this study was to assess and compare the efficiency of dry needling, lidocaine injection and oral flurbiprofen treatments in patients with myofascial pain syndrome (MPS) involving the neck and back region. Patients and methods: A total of 60 patients (7 males, 53 females; mean age 33.7 years; range 18 to 50 years) were included in this prospective study. The patients were divided into three groups by block randomization. Each group was assigned to dry needling for trigger points, lidocaine injection (double blind) or oral flurbiprofen 200 mg/day over seven days. All patients were also prescribed a standardized home exercise program based on stretching of the affected muscles. Before treatment and on the third and 14 days after treatment, pain severity was assessed by visual analog scale (VAS), degree of tenderness at the trigger points by algometry, active joint range of motion of the neck and shoulders by goniometry, and the quality of life by Nottingham Health Profile. Results: There was a significant improvement in pain severity, trigger point tenderness, joint range of motion, and quality of life in all three groups on the third and 14th days of treatment. No significant difference was found in treatment efficiency among the groups. Conclusion: Treatments with dry needling, lidocain injection and oral flurbiprofen along with home exercises are all effective in the management of MPS.